The bronze screen : Chicana and Chicano film culture - Fregoso, Rosa Linda (Minneapolis : University of Minnesota Press, 1993)
Explores Chicana and Chicano popular culture through contemporary representations in both Hollywood commercial and independent cinema.
List of Photographs; Acknowledgments; Introduction: The Bronze Screen: Looking at Us Looking; 1 Actos of "Imaginative Re-discovery"; 2 Intertextuality and Cultural Identity in Zoot Suit (1981) and La Bamba (1987); 3 Humor as Subversive De-construction: Born in East L.A. (1987); 4 From Il(l)egal to Legal Subject: Border Construction and Re-construction; 5 Nepantla in Gendered Subjectivity; 6 Conclusion: Eastside Story Re-visited; Notes; Index.
Includes bibliographical references and index.
Print version record.
English.
JSTOR
Keywords: Culture in motion pictures; Mexican Americans in motion pictures; Culture au cinéma.; Américains d'origine mexicaine au cinéma.; PERFORMING ARTS -- Film & Video -- General; PERFORMING ARTS -- Reference; POLITICAL SCIENCE -- Essays; POLITICAL SCIENCE -- Government -- General; POLITICAL SCIENCE -- Government -- National; POLITICAL SCIENCE -- Reference; Culture in motion pictures; Mexican Americans in motion pictures